2011
DOI: 10.1038/ejcn.2011.62
|View full text |Cite
|
Sign up to set email alerts
|

Dairy consumption and risk of type 2 diabetes mellitus: a meta-analysis of cohort studies

Abstract: Background/Objectives: Milk intake is widely recommended for a healthy diet. Epidemiological studies have suggested that the consumption of dairy products may be associated with a reduction in type 2 diabetes mellitus (T2DM). A meta-analysis was conducted to elucidate the association between dairy products consumption and T2DM. Subjects/Methods: A systematical literature search was done through the Medline database and seven related cohort studies were identified. The adjusted relative risks (RRs) with the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
194
3
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 257 publications
(223 citation statements)
references
References 26 publications
15
194
3
6
Order By: Relevance
“…Similarly, Villegas et al (34) reported that compared with nonconsumers, the RR (95% CI) for type 2 diabetes was 0.61 (0.54-0.69) for women consuming ,100 g/day of milk and 0.74 (0.67-0.82) for women consuming powdered milk in the Shanghai Women's Health Study. These associations among Chinese populations seemed stronger than those from a previous meta-analysis, which showed that the risk of type 2 diabetes was 14% lower in the highest quintile of total dairy consumption compared with the lowest quintile (5,35). Several recent studies, on the other hand, did not find significant associations between dairy product consumption and diabetes (8)(9)(10)(11)(12).…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Similarly, Villegas et al (34) reported that compared with nonconsumers, the RR (95% CI) for type 2 diabetes was 0.61 (0.54-0.69) for women consuming ,100 g/day of milk and 0.74 (0.67-0.82) for women consuming powdered milk in the Shanghai Women's Health Study. These associations among Chinese populations seemed stronger than those from a previous meta-analysis, which showed that the risk of type 2 diabetes was 14% lower in the highest quintile of total dairy consumption compared with the lowest quintile (5,35). Several recent studies, on the other hand, did not find significant associations between dairy product consumption and diabetes (8)(9)(10)(11)(12).…”
Section: Discussioncontrasting
confidence: 45%
“…However, only some prospective studies have observed inverse associations between dairy consumption and risk of diabetes (5-7), whereas others reported null findings (5,(8)(9)(10)(11)(12). In this regard, prospectively investigating associations between dairy consumption and cardiometabolic traits related to diabetes may shed light onto the relationship between dairy consumption and risks of diabetes.…”
mentioning
confidence: 99%
“…Nevertheless, consumption of dairy foods (especially lowfat dairy), which are good sources of both calcium and magnesium, may have a role in diabetes prevention. 12 Of note, our study was not designed or powered to separate the independent effect of magnesium on the calcium-diabetes association, because the analysis was based upon published studies using various multivariable models. Moreover, the high correlation between dietary calcium and magnesium in some individual studies made it difficult to separate their independent effects.…”
Section: Discussionmentioning
confidence: 99%
“…For example, fermented dairy products have been associated with reduced risk of type 2 diabetes or improved markers of glucose homeo stasis, [24][25][26] less weight gain over time in a prospective study of >120,000 adults 27 and reduced risk of overall mortal ity. 28 An observational study of >6,500 indivi duals found that yogurt consumers had reduced levels of circulat ing triglycerides and glucose, as well as reduced systolic blood pressure and insulin resistance, compared with non consumers.…”
Section: Q Should the Probiotic Framework Include Traditional Fermentmentioning
confidence: 99%